2017
DOI: 10.2147/ijn.s139212
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of selenium nanoparticles using<em> Acinetobacter</em> sp. SW30: optimization, characterization and its anticancer activity in breast cancer cells

Abstract: The aim of this study was to synthesize selenium nanoparticles (SeNPs) using cell suspension and total cell protein of Acinetobacter sp. SW30 and optimize its synthesis by studying the influence of physiological and physicochemical parameters. Also, we aimed to compare its anticancer activity with that of chemically synthesized SeNPs in breast cancer cells. Cell suspension of Acinetobacter sp. SW30 was exposed to various physiological and physicochemical conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(95 citation statements)
references
References 46 publications
6
89
0
Order By: Relevance
“…Reports on chemically synthesized SeNP suggested lower toxicity and equivalent anticancer activity compared to inorganic and organic selenium compounds (3,11,21,22). Similarly, biogenic SeNPs synthesized by Acinetobacter, Streptomyces, and Halococcus also showed anticancer activity, however, at higher doses (13)(14)(15). Earlier in our study, we have shown that a concentration of 2 µg Se/ml of our sterically stabilized biogenic SeNPs is very effective in inducing TNF/IRF1 mediated necroptosis in PC-3 cells without compromising the viability of human peripheral blood mononuclear cell (hPBMC) (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on chemically synthesized SeNP suggested lower toxicity and equivalent anticancer activity compared to inorganic and organic selenium compounds (3,11,21,22). Similarly, biogenic SeNPs synthesized by Acinetobacter, Streptomyces, and Halococcus also showed anticancer activity, however, at higher doses (13)(14)(15). Earlier in our study, we have shown that a concentration of 2 µg Se/ml of our sterically stabilized biogenic SeNPs is very effective in inducing TNF/IRF1 mediated necroptosis in PC-3 cells without compromising the viability of human peripheral blood mononuclear cell (hPBMC) (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…The greater biocompatibility and better stability of these particles are reported to be due to the differential nanostructural arrangements of selenium atoms (12). Some biogenic SeNPs are also reported to induce cell death in various cancer cell lines including Hep-G2, MCF-7, 4T1, and HeLa (13)(14)(15). However, their effect was observed at higher doses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, experiments with isolated proteins, presumably involved in metals reduction, have been performed and the results have shown that metals reduction is linked to those specific proteins . In addition, proteins have been reported to be responsible for the reduction and stabilization of NPs acting as capping agents …”
Section: Mechanisms Involved In the Microbial Synthesis Of Npsmentioning
confidence: 99%
“…11,16,43 In addition, proteins have been reported to be responsible for the reduction and stabilization of NPs acting as capping agents. 15,21,37,40 Enzymes, such as reductases, flavoenzymes, oxidoreductases, hydrogenases, amylases, etc., have been associated with metals reduction. Enzyme activity in culture supernatant evinced participation of extracellular enzymes in metallic NPs biosynthesis.…”
Section: Mechanisms Involved In the Microbial Synthesis Of Npsmentioning
confidence: 99%
See 1 more Smart Citation